Kepentingan Ekonomi Politik Usaha Kecil di Malioboro, Yogyakarta [The Political Economy of Small Enterprises in Malioboro, Yogyakarta] - Muh Kamim, Anggalih Bayu (Sekretariat Jenderal DPR RI, 2023)
This study is aimed to explore the vulnerability of small enterprises in Malioboro that depend on mass tourism. The research question is how did the political economy of small enterprises in Malioboro change? Data collection was carried out by in-depth online interviews with small enterprise actors in Malioboro due to the Covid-19 pandemic situation. Data was also collected through searches of journal articles, manuscripts, government reports, online media reports, and books related to economic development of Malioboro. The results of the study show that the growth of small enterprises in Malioboro since the 18th century is related to the commodification of urban space around Pasar Gedhe. Massive development of urban infrastructure and the growth of tourism driven by the colonial government since the 19th century have encouraged the emergence of the